(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The article discusses adequate assessment of the energy efficiency of using a variable frequency drive in pumping units in the technology of underground leaching of minerals, energy-efficient control methods, taking into account the specific features of the technology and design features of electric drives of pumping units used in the technology of underground leaching.